Intelligent design: nascita e sviluppo del movimento - Bedetti, Matteo (Nuovo giornale di filosofia della religione, 2020)
The following article is going to discuss the Intelligent Design movement, which was born in the United States during the last decade of the twentieth century and became famous because of its critical statements toward Evolutionism. The main goal of this article is to expose, in a neutral way, the history of the movement, its topics, its supporters and critics. In the beginning, the article deals with the precursors of the Intelligent Design and the history of the Discovery Institute, organization which the exponents of the movement are part of. It follows the analysis of the reception of the Intelligent Design in Italy. The subsequent topic of the article is the thoughts of the most eminent members of the Discovery Institute: William Dembski, Michael Behe, Stephen Meyer and Douglas Axe. The final part focuses on the critics of the Intelligent Design, in particular the philosophers of science Telmo Pievani and Benjamin Jantzen.